Progressive muslims' approach to hadith texts : a critical evaluation - Nurul Jannah Zainan Nazri (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2013)
Questions on the authenticity of Sunnah have long been of central importance to the study of Islam. Among the crucial points that are fiercely debated in this matter is the issue of textual criticism, which appears to have the effect of discrediting the existing record of Sunnah. This study explains and clarifies the relevance of the classical methodology of hadith text criticism in modern times. By using the case of Progressive Islam as the focal-point, it explores the impact of modernity on contemporary Muslims' attitudes towards religious authorities especially the hadith of the Prophet r. It traces back the intellectual origin of Progressive Muslims' approach to hadith texts and investigates its salient features. It also examines the extent to which this so-called new approach is in line with the classical hadith scholars' methodology. It assesses the interpretational implications of their approach to hadith related to the Islamic belief system ('aqidah), metaphysical issues (ghaybiyyat) and Muslim social affairs (women and racist issues). In a nutshell, this work provides a major contribution to the understanding of the attitudes of the modernists in particular the Progressive Muslims towards the Prophetic texts in modern times.